PENEROBOSAN TERHADAP BATAS-BATAS KEBEBASAN KEKUASAAN KEHAKIMAN - I Gusti Ketut Ariawan (Masalah-Masalah Hukum, 2010)
Question of free Judicial Power are deemed completed when there is agreement (consensus) of the scientific principle of freedom of the judiciary, which is universal, because it has been accepted through the doctrine and constitution. Scientific consensus on the freedom of judiciary actually don't do discourse or legal discourse is stopped at one point, but in fact it triggers a new discourse that is abuse of the freedom of judicial power. Misuse ofpoweris manifested in the form of arbitrariness on the part of the Supreme Court in the form of creating "new law", which was born out of the office and the authority. In an effort to create the new law, sometimes the Supreme Court made a decision that really significant "contrary to Law". The abuse of judicial power appears in the Supreme Court decision No.275 K/Pmd/1983, that "smoking can be petitioned for an appeal by the prosecutor", and the decision of the Judicial Review No 55/Pid/1996 on the judicial review may be classified as a decision containing prescriptive-ratio (matter of law), that is the new law, recognizes the authority of the prosecutor to filed a judicial review. In its decision the Supreme Court has been remarkably free to abuse the freedom of the judiciary, which the Supreme Court had violated the criminal procedure code (KUHAP), on the creation of new legal regulations. Supreme Court actually has exceeded its competence by taking arbitrarily the competence of legislator, because in essence to the new law that created are publicly binding